2018
DOI: 10.32677/ijch.2018.v05.i02.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cord bilirubin and bilirubin albumin ratio to predict significant hyperbilirubinemia in healthy full-term neonates

Abstract: Background: Early prediction and identification of severe hyperbilirubinemia for that age and appropriate treatment are must to prevent kernicterus. Objective: The objective is to study the predictive value of bilirubin albumin ratio (BAR) and to compare it with cord bilirubin alone for early identification of significant neonatal hyperbilirubinemia in healthy term neonates. Materials and Methods: This prospective cross-sectional study was done in a tertiary care center located in Central India on 543 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…This also comes in agreement with EL Mashad et al, [17] who found that bilirubin/albumin ratio is a useful predictor for occurrence of jaundice; a cutoff level of cord blood bilirubin/ albumin of 0.82 had 88.9% sensitivity, 85.7% specificity, PPV 94.1% and NPV of 75% and also comes in agreement with Bhat J. et al [20] who conducted their study on neonates with gestational age ≥ 35w and Ramteke S et al, [15] on healthy term neonates and found the same results. This can be explained as the bilirubin/albumin ratio B/A might provide a better estimate of free bilirubin because it contains 2 of the 3 factors determining free bilirubin (TSB, albumin and the albumin binding affinity) [21].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This also comes in agreement with EL Mashad et al, [17] who found that bilirubin/albumin ratio is a useful predictor for occurrence of jaundice; a cutoff level of cord blood bilirubin/ albumin of 0.82 had 88.9% sensitivity, 85.7% specificity, PPV 94.1% and NPV of 75% and also comes in agreement with Bhat J. et al [20] who conducted their study on neonates with gestational age ≥ 35w and Ramteke S et al, [15] on healthy term neonates and found the same results. This can be explained as the bilirubin/albumin ratio B/A might provide a better estimate of free bilirubin because it contains 2 of the 3 factors determining free bilirubin (TSB, albumin and the albumin binding affinity) [21].…”
Section: Discussionsupporting
confidence: 87%
“…Concerning cord blood bilirubin; our data showed that there was positive significant correlation between the cord blood bilirubin levels and the incidence of significant indirect hyperbilirubinemia on the 3 rd day in the two studied groups (P value < 0.001) and also the duration of phototherapy in the two studied groups. This comes in agreement with Khairy et al [7] who conducted their study on full term neonates, Ramteke S et al [15] on healthy term neonates, Ipek et al [16] on full term neonates and EL Mashad et al, on 75 neonates with gestational age ≥ 35w and found a highly significant increase in the cord serum bilirubin levels in babies who developed significant neonatal hyperbilirubinemia [17].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, a previous study reported a cord blood bilirubin/albumin ratio cut-off of 0.82, as obtained by ROC curve, and with 88.9% sensitivity, 85.7% specificity, PPV 94.1%, and NPV 75% for predicting neonatal hyperbilirubinemia in a high-risk group. 15 Ramteke et al 21 derived a 0.89 cut-off point of cord bilirubin/albumin ratio, and suggested that 95.5% of patients will likely develop future neonatal NNH if their ratio is above 0.89.…”
Section: Discussionmentioning
confidence: 99%